KESALAHAN UMUM YANG DILAKUKAN SISWA SMA KELAS 1 PADA PENULISAN KALIMAT SIMPLE PRESENT TENSE - Widayanti, Maria J.A. (Universitas Negeri Semarang, 2008)
The research was a descriptive qualitative research. The research process wasstarted by doing an observation among students in applying the basic concept ofsimple present tense in their daily activities. Before analyzing the research, theresearchers did some observations, try out test, collecting data, and interview amongstudents. The researchers found out that more than 80% students could not understandthe basic concepts of simple present tense well. They often did some grammaticalerrors. Its topic was chosen based on the researchersÃ¢â¬â¢ experience as the Englishteachers. The researchers often found studentsÃ¢â¬â¢ grammatical errors especially insimple present tense. The aim of the research was formulated as: (1). To know howstudents can understand and make the simple present tense in positive, negative, andinterrogative form both in singular and plural subject at the written test, (2). To knowwhat kinds of grammatical errors were used to be done by students in creating thesimple present tense sentences at the interview test, (3). What kinds of general errorswere used to be done by students. The research was located at 2 Senior High Schoolon Jalan Sendangguwo Baru no 1, Semarang. The subject of this research was the firstgrade students of 2 Senior High School. The samples were taken randomly from eachclass (20% from the total population). The techniques of collecting data were done bywritten and interview test. The collecting data were done three times. At the first,students were asked to answer the essay test, at the second, students were asked towrite down their daily activities in English Language. Then at the third, students wereasked to tell their daily activities orally. The results of the test were: at the try out test,there were only 12 of 42 students (30%) who could do and write the simple presenttense sentences correctly. On the collecting data test, there were 32 of 42 students(65%) who could do and write the simple present tense sentences correctly. It could besaid that there was an improvement to understand the basic concept of simple presenttense among students (35%). While at the interview test, students were used to doovergeneralization and incomplete application of rules as their common mistakes.Kata kunci: simple present tense, overgeneralization, incomplete application of rules